Effect of KIBRA on tau‐mediated synaptic and memory deficits. (1st February 2022) - Kauwe, Grant; Pareja‐Navarro, Kristeen; Chen, Jackson; Li, Yaqiao; Le, David; Zhou, Yungui; Gan, Li; Tracy, Tara E
Abstract: Background: Alzheimer's disease (AD) is characterized by an accumulation of tau in the brain and progressive memory decline. Previous work showed that aberrant acetylation of K274 and K281 on tau in postmortem human AD brains is linked to dementia. Transgenic mice expressing human tau with mutations to mimic acetylation at K274 and K281 (tauKQ) have impaired long‐term potentiation (LTP) and exhibited hippocampal‐dependent memory deficits. Postsynaptic protein levels of KIdney/BRAin (KIBRA) are reduced in tauKQ mice and lower KIBRA protein levels are associated with dementia in human AD brains. KIBRA is a scaffolding protein containing several protein binding domains involved in multiple signaling pathways that regulate neuronal function. Our research aims to uncover how dysregulation of KIBRA signaling contributes to the loss of synaptic plasticity in AD and whether KIBRA signaling can be targeted for therapeutic intervention to prevent memory loss. Method: We generated an N‐terminal fragment of KIBRA (N‐term KIBRA) and C‐terminal fragment of KIBRA (C‐term KIBRA) that were expressed either in dissociated rat hippocampal cultures or in vivo using lentivirus‐mediated expression in tauKQ mice. We performed immunostaining, electrophysiology, and mouse behavior experiments to examine the effects of either N‐term KIBRA or C‐term KIBRA on neurons expressing pathogenic tau. Result: We found that C‐term KIBRA restores AMPAR trafficking during LTP in neurons expressing pathogenic tau. N‐term KIBRA failed to restore AMPAR trafficking required for LTP. We injected lentivirus expressing C‐term KIBRA in the hippocampus of tauKQ mice and found that C‐term KIBRA restored LTP and hippocampal‐dependent memory deficits in tauKQ mice. C‐term KIBRA interacts with the brain‐specific kinase protein kinase Mζ (PKMζ), and PKMζ is required for C‐term KIBRA rescue of AMPAR trafficking during LTP in neurons expressing pathogenic tau. Conclusion: We have shown that the C‐terminus region of KIBRA can restore LTP and memory impairments in mice with pathogenic tau that mimics the accumulation of acetylated tau in AD brain. Our work suggests C‐term KIBRA enhances synaptic plasticity through a direct interaction with PKMζ to modulate AMPAR trafficking.